Aktivitas Sucrose Phosphate Synthase dan Kandungan Sukrosa pada Tanaman Tebu Trangenik Hasil Perbanyakan Secara Vegetatif - Wiwik Sri Untari (Program Studi Agribisnis Fakultas Pertanian, 2013)
Sugar Cane (Saccharum officinarum L) is one of the estate commodity which developed because ability in sucrose synthesis and sucrose accumulation. Sucrose Phosphate Synthase (SPS) is a key enzym of sucrose biosynthesis in cytosol. SPS gene transformation was expected increase sucrose synthesis and accumulation in sugar cane. Genetic stability of transgenic sugar cane was studied on the several generation. The objective of the research investigated the existence of CaMV promoter, SPS activity and sucrose in transgenic sugar cane leaf after three periode of derived vegetative propagation.This research was divided into four phase, included DNA isolation, SPS activity, sucrose analysis in sugar cane leaf and yield analysis after 11 month of sugar cane. The result showed that the 25,47% of transgenic sugar cane expressed CaMV promoter by PCR analysis. SPS activity and sucrose content in transgenic sugar cane leaf were higher more than control (r = 0,364). transgenic sugar cane maturely was linger more than control.